Association between Parkinson’s disease and the faecal eukaryotic microbiota - Severin Weis (Nature Portfolio, 2021)
Abstract Parkinson’s disease (PD) is one of the most common neurodegenerative disease, and is so far not considered curable. PD patients suffer from several motor and non-motor symptoms, including gastrointestinal dysfunctions and alterations of the enteric nervous system. Constipation and additional intestinal affections can precede the classical motor symptoms by several years. Recently, we reported effects of PD and related medications on the faecal bacterial community of 34 German PD patients and 25 age-matched controls. Here, we used the same collective and analysed the V6 and V7 hypervariable region of PCR-amplified, eukaryotic 18S rRNA genes using an Illumina MiSeq platform. In all, 53% (18) of the PD samples and 72% (18) of the control samples yielded sufficient amplicons for downstream community analyses. The PD samples showed a significantly lower alpha and a different beta eukaryotic diversity than the controls. Most strikingly, we observed a significantly higher relative abundance of sequence affiliated with the Geotrichum genus in the PD samples (39.7%), when compared to the control samples (0.05%). In addition, we observed lower relative abundances of sequences affiliated with Aspergillus/Penicillium, Charophyta/Linum, unidentified Opisthokonta and three genera of minor abundant zooflagellates in the PD samples. Our data add knowledge to the small body of data about the eukaryotic microbiota of PD patients and suggest a potential association of certain gut eukaryotes and PD.